The - Sekfali, Badiaa (Smith, Bonappétit & Son, 2007)
Once upon a time, there were a king and queen who were childless. By an unfortunate twist of fate, God sent them a small chick as an heir. Months passed and that chick became a rooster, who wanted a wife. Many young women attracted by the royal rewards presented themselves, but only when one of them showed real interest in the rooster did the marriage take place. In the nuptial chamber, a miracle happened and a beautiful prince emerged from under the feathers. But by recounting her adventure to her mother, the young woman broke the promise she had made to her husband, forcing him to flee. Then began a long and hard quest to find her loving husband ...